Pelatihan Desain UI/UX Mobile Apps Untuk Remaja Masjid Jakarta Islamic Centre Menggunakan Figma - Nurmalasari Nurmalasari; Riyan Latifahul Hasanah (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
Jakarta Islamic Center (JIC) is a local government institution that includes elements of local government and society with main tasks including human resources development, information and communication and business development. In the information and communication function, JIC requires a medium that can be used for broadcasting Islamic proselytizing optimally and managed professionally with an attractive and up to date appearance. Therefore, a team of lecturers from the Faculty of Information Technology, Nusa Mandiri University (FTI UNM) conducted community service in the form of training on how to design UI / UX with figma on mobile apps for JIC mosque teenagers. The training was held on October 15, 2022 at the Damai campus with 14 participants through presentations, demonstrations, discussions and questions and answers. The results of the research can equip new knowledge and knowledge for participants so that they have skills in creating and managing information and communication media in the form of mobile apps with attractive designs and in accordance with the needs of visitors